Analisis Potensi Pajak Restoran di Kota Bengkulu - Sahuddin Sahuddin; Pakri Fahmi; Syaiful Anwar (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2018)
Restaurant tax is one of the taxes that are the authority of local government. In the city of Bengkulu, restaurant taxes ranked fourth with contributions of 9.63 percent. This study aims to analyze the acceptance and potential of Restaurant Tax in Bengkulu City. The results of the study indicate that the acceptance of restaurant taxes in the city of Bengkulu is still below the true potential. The structure of tax revenue is dominated by the categories of restaurants and cafes, which contributes about 92.6 percent, while the stalls and restaurants contribute 7.4 percent, whereas in quantity the number of taxpayers stalls and restaurants is much larger, reaching 85,3 percent of all existing taxpayers. The main sources of tax increase have been pointed out, among other things, from potential new restaurant tax sources, particularly in restaurant and cafÃ© categories. Based on trend analysis and average value approach of actual payment ratio and tax potential, the tax potential of restaurants in Bengkulu city for 2017 is estimated to be around Rp 6.5 billion and will continue to increase to Rp. 9.7 billion in 2021